Encuentros y desencuentros del estado local y regional en la gestión integrada de los residuos sólidos. Una tarea pendiente en el Valle Sagrado - Tupayachi Mar, Teresa (2012)
This article and the following «The Material Politics of Waste Disposal - decentralization and integrated systems» from Penelope Harvey are published as complementary accounts on the management of solid waste in the Vilcanota Valley in Cusco. Penelope Harvey and Teresa Tupayachi worked together on this theme. In this paper, Tupayachi introduces the legal framing for the politics of waste disposal in the region. She also presents two studies that were commissioned in order to find solutions to the problem of waste disposal. The first was carried out in 2003, with finance from Finnish development cooperation funds, in co-ordination with technical experts from various universities, NGOs and state agencies, including the municipality of Urubamba. The second, a component of the Vilcanota project, was completed in 2011. The studies have things in common. Both involve regional and local government as central agents in the process, both focus their efforts to resolve the problem of solid waste management on possible technical solutions, and both are well resourced in both financial and human terms. However neither succeed in finding a way to accommodate the diverse interests and perceptions of the municipalities and of the general public. Faced with this situation local government officials, and people in general act on their own initiative, finding decentralized, and at times informal solutions to the problem, taking advantage of market opportunities.